Study of plasmonics in hybrids made from a quantum emitter and double metallic nanoshell dimer. (10th April 2018) - Guo, Jiaohan; Black, Kevin; Hu, Jiawen; Singh, Mahi
Abstract: We developed a theory for the fluorescence (FL) for quantum emitter and double metallic nanoshell dimer hybrids using the density matrix method. The dimer is made from two identical double metallic nanoshells, which are made of a dielectric core, a gold metallic shell and a dielectric spacer layer. The quantum emitters are deposited on the surface of the spacer layers of the dimers due to the electrostatic absorptions. We consider that dimer hybrids are surrounded by biological cells. This can be achieved by injecting them into human or animal cells. The surface plasmon polaritons (SPP) are calculated for the dimer using Maxwell's equations in the static wave approximation. The calculated SPP energy agrees with experimental data from Zhai et al (2017 Plasmonics 12 263) for the dimer made from a silica core, a gold metallic nanoshell and a silica spacer layer. We have also obtained an analytical expression of the FL using the density matrix method. We compare our theory with FL experimental data from Zhai et al (2017 Plasmonics 12 263) where the FL spectrum was measured by varying the thickness of the spacer layer from 9 nm to 40 nm. A good agreement between theory and experiment is found. We have shown that the enhancement of the FL increases as the thickness of the spacer layer decreases. We have also found that the enhancement of the FL increases as the distance between the double metallic nanoshells in the dimer decreases. These are interesting findings which are consistent with the experiments of Zhai et al (2017 Plasmonics 12 263) and can be used to control the FL enhancement in the FL-based biomedical imaging and cancer treatment. These interesting findings may also be useful in the fabrication of nanosensors and nanoswitches for applications in medicine.